2019
DOI: 10.1016/j.neuropsychologia.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of infant event related potentials evoked by faces

Abstract: Reliable measures are required to draw meaningful conclusions regarding developmental changes in longitudinal studies. Little is known, however, about the test-retest reliability of face-sensitive event related potentials (ERPs), a frequently used neural measure in infants. The aim of the current study is to investigate the test-retest reliability of ERPs typically evoked by faces in 9-10 month-old infants. The infants (N=31) were presented with neutral, fearful and happy faces that contained only the lower or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 22 publications
8
44
5
Order By: Relevance
“…This is taken to suggest that children rely on different frequency information and might need more detailed feature-focused information than adults when processing fearful facial expressions. This developmental view has been confirmed by a recent ERP study with 9-to-10-month-old infants showing that infants at this age also predominantly use HSF to discriminate happy, fearful and neutral facial expressions (Munsters et al, 2017 ). Specifically, this study revealed differential processing of emotional facial expressions in response to HSF images but not for LSF images.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…This is taken to suggest that children rely on different frequency information and might need more detailed feature-focused information than adults when processing fearful facial expressions. This developmental view has been confirmed by a recent ERP study with 9-to-10-month-old infants showing that infants at this age also predominantly use HSF to discriminate happy, fearful and neutral facial expressions (Munsters et al, 2017 ). Specifically, this study revealed differential processing of emotional facial expressions in response to HSF images but not for LSF images.…”
Section: Introductionmentioning
confidence: 58%
“…However, emotion discrimination from faces, in particular involving fearful faces, typically affects additional ERP components and can be reliably observed already in infants at a younger age (Peltola et al, 2009 , 2013 ) than in Munsters et al ( 2017 ) study, who investigated emotion processing in 9- to 10-month-old infants. Moreover, spatial frequency filtering might need to be adjusted to take into account the visual acuity at the age under investigation (Dobkins and Harms, 2014 ), which had not been done in the prior study with infants that used spatial frequency cut-offs typically used with adults (Munsters et al, 2016 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In response to the replication crisis in cognitive sciences, cognitive neuroscientists have begun to show a growing interest in the test-retest reliability of their paradigms and brain measures, and several recent studies have assessed the test-retest reliability of EEG measurements in infants. Munsters et al (2019) reported the test-retest reliability of ERPs evoked by neutral, fearful and happy faces presented in low or high-frequency conditions to 9-10 month-old infants (N=31), who were tested twice within two weeks. Substantial reliability was observed for the amplitude of the earliest N290 component (Intraclass correlation (ICC)=0.76), and moderate reliability was observed for the amplitude of components P400 (ICC=0.58) and Nc (ICC=0.57) (see Figure 8A).…”
Section: Problemmentioning
confidence: 99%